Taxonomic notes on Amaurobius (Araneae: Amaurobiidae), including the description of a new species - Marusik, Yuri M.; Otto, S.; Japoshvili, G. (Zootaxa, 2020)
A new species, Amaurobius caucasicus sp. n., is described based on the holotype male and two male paratypes from Eastern Georgia. A similar species, A. hercegovinensis Kulczyński, 1915, known only from the original description is redescribed. The taxonomic status of Amaurobius species considered as nomina dubia and species described outside the Holarctic are also assessed. Amaurobius koponeni Marusik, Ballarin & Omelko, 2012, syn. n. described from northern India is a junior synonym of A. jugorum L. Koch, 1868 and Amaurobius yanoianus Nakatsudi, 1943, syn. n. described from Micronesia is synonymised with the titanoecid species Pandava laminata (Thorell, 1878) a species known from Eastern Africa to Polynesia. Considerable size variation in A. antipovae Marusik et Kovblyuk, 2004 is briefly discussed.